Impacts of exoprosthesis use in dogs with partial amputation and limb malformations: a systematic review - Souza, Miriã Mamede Noronha de; Lima, Jackson Nazareno Gomes de; Menezes, Danilo José Ayres de; Carvalho, Lucas Rannier Ribeiro Antonino (Frontiers in Veterinary Science, 2025)
IntroductionCongenital malformations and limb amputations are common causes of locomotor impairment in dogs, affecting their mobility and well-being. Exoprostheses reemerge as a promising alternative for restoring locomotor function and improving animal welfare. This study aimed to conduct a systematic review of the impacts of exoprostheses used in dogs with limb amputations or malformations.MethodsThe research followed PRISMA guidelines, with searches conducted in PubMed, Web of Science, and SciELO databases, using terms related to dogs, prosthetics, 3D printing, and locomotion. Original articles with clinical applications of socket-type exoprostheses in dogs, made by 3D printing or similar materials, were included. Studies without direct clinical data, implantable prostheses, and assistive devices were excluded. The selection was made independently by two reviewers, and the snowballing strategy broadened the analysis.ResultsAfter screening and analysis, ten articles were included for synthesis. Among these studies, the main causes of amputation were trauma, congenital deformities, and neoplasms, affecting both thoracic and pelvic limbs. Regarding the exoprosthesis manufacturing approach, most studies used the traditional method of vacuum forming a thermoplastic over a positive form, and three describe the use of 3D printing as an alternative to producing animal prostheses. The studies reported significant improvements in dogs’ mobility and quality of life, although complications such as skin lesions and difficulties with fixation were reported, necessitating adjustments and ongoing veterinary supervision.DiscussionCustomized exoprostheses offer effective and affordable solutions for dogs with amputations, promoting functional improvements and well-being. Further research is warranted to enhance durability and establish standardized protocols for clinical use.